Plasma Vitamin C Concentrations and Cognitive Function: A Cross-Sectional Study - Travica, Nikolaj; Ried, Karin; Sali, Avni; Hudson, Irene; Scholey, Andrew; Pipingas, Andrew (Frontiers in Aging Neuroscience, 2019)
Vitamin-C is a water soluble molecule that humans have lost the ability to produce. Vitamin-C plays a role in CNS functions such as neuronal differentiation, maturation, myelin formation and modulation of the catecholaminergic systems. A recent systematic review by our team indicated the need for further research into the relationship between plasma vitamin C and cognition in cognitively intact participants using plasma vitamin C concentrations instead of estimates derived from food-frequency-questionnaires (FFQ), and more sensitive cognitive assessments suitable for cognitive abilities vulnerable to aging. It was hypothesized that higher plasma vitamin C concentrations would be linked with higher cognitive performance. This cross-sectional trial was conducted on healthy adults (n = 80, Female = 52, Male = 28, 24–96 years) with a range of plasma Vitamin C concentrations. Cognitive assessments included The Swinburne-University-Computerized-Cognitive-Assessment-Battery (SUCCAB) and two pen and paper tests, the Symbol-Digits-Modalities-Test (SDMT) and Hopkins-Verbal-Learning-Test-Revised (HVLT-R). The pen and paper assessments were conducted to establish whether their scores would correlate with the computerized tasks. Plasma-Vitamin C concentrations were measured using two biochemical analyses. Participants were grouped into those with plasma vitamin-C concentrations of adequate level (≥28 μmol/L) and deficient level (<28 μmol/L). The SUCCAB identified a significantly higher performance ratio (accuracy/reaction-time) in the group with adequate vitamin-C levels vs. deficient vitamin-C on the choice reaction time (M = 188 ± 4 vs. 167 ± 9, p = 0.039), immediate recognition memory (M = 81 ± 3 vs. 68 ± 6, p = 0.03), congruent Stroop (M = 134 ± 3 vs. 116 ± 7, p = 0.024), and delayed recognition tasks (M = 72 ± 2 vs. 62 ± 4, p = 0.049), after adjusting for age (p < 0.05). Significantly higher scores in immediate recall on the HVLT-R (M = 10.64 ± 0.16 vs. 9.17 ± 0.37, p = 0.001), delayed recall (M = 9.74 ± 0.22 vs. 7.64 ± 0.51, p < 0.001), total recall (M = 27.93 ± 0.48 vs. 24.19 ± 1.11, p = 0.003) were shown in participants with adequate plasma Vitamin-C concentrations, after adjusting for vitamin-C supplementation dose (p < 0.05). Similarly, higher SDMT scores were observed in participants with adequate plasma Vitamin-C concentrations (M = 49.73 ± 10.34 vs. 41.38 ± 5.06, p = 0.039), after adjusting for age (p < 0.05). In conclusion there was a significant association between vitamin-C plasma concentrations and performance on tasks involving attention, focus, working memory, decision speed, delayed and total recall, and recognition. Plasma vitamin C concentrations obtained through vitamin C supplementation did not affect cognitive performance differently to adequate concentrations obtained through dietary intake. Clinicaltrials.gov Unique Identifier: ACTRN 12615001140549, URL: https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=369440.